State-level reforms in India : towards more effective government - India States Reform Forum: Fiscal and Governance Reforms for Poverty Reduction (2000 : Delhi, India); Howes, Stephen; Lahiri, Ashok K.; Stern, N. H. (New Delhi : Macmillan India, 2003)
Contributed papers presented at India States Reform Forum: Fiscal and Governance Reforms for Poverty Reduction, held in November 2000, at Delhi.
Includes bibliographical references.
Newaz
Keywords: State governments -- India -- Congresses; Poverty -- Government policy -- India -- Congresses